SALMAN RUSHDIE‟S NOVEL MIDNIGHT‟S CHILDREN: AN ACCOUNT OF RETRACING HISTORICAL EVENTS FOR AUTHENTICITY - V, Jayalakshmi; R , Subha; R , Subha (International Journal of Psychosocial Rehabilitation, 2020)
History is the collection of the events of the past that is recorded and preserved for the understanding of ancient times. Understanding the history is necessary to understand the present but not all the history is recorded objectively. History at all times may not be the mere collection of facts it may be sometimes what historians write. Thus the authenticity of the history has to be examined. Salman Rushdie in his famous novel Midnight’s children has made an attempt to record the events of the history through the experience of his protagonist Saleem Sinai. Salman Rushdie is an Indian born British novelist and essayist popular for his historical fiction most of it set in Indian subcontinent. With the blend of magical realism and self-reflexive style Salman Rushdie published Midnight’s Children in 1981 that fetched him Booker Prize and was deemed to be "the best novel of all winners". The novel deals with the journey of India from British colonialism to independence and the partition of India. This paper analyses the authenticity of the history by retracing the events recorded by Salman Rushdie in his novel Midnight’s Children.